Adsorption and biomass concentration of thraustochytrid Schizochytrium aggregatum (Goldstein and Belsky) in bunker C oil - Sarinas Brian Gil S.; Gellada, Lorna D.; Torrigue, Ma. Lona T.; Sibonga, Dolores N.; Torrato, Edmar S.; Malagad, John G.; Feril, Joseph G.; Bondoc, Lyle Arianne J.; Roncal, Juan Clemente A.; Tornalejo, Jilla A. (2014)
Diverse array of microorganisms such as bacteria, fungi and protists are involved during oil spill. Each microorganism has its own specific function whether it has to degrade or adsorb hydrocarbons. One important microorganism is the Thraustochytrid that is a fungoid protist and are common in marine and estuarine habitats. Numerous studies existed on the biodegradation and adsorption of Thraustochytrids on various substances but not on Bunker C oil. Thus, this study aimed to determine the adsorption capacity and mean biomass of Thraustochytrids in Banker C oil using different cell densities measured in grams. All of the three treatments or cell densities (1x105 cells ml-1, 1x106 cells ml-1 and 1 x 107 cells ml-1) were triplicated and average values were recorded. Oil dispersant was used as a control. It showed that Thraustochytrid with 1x107 cells ml-1 showed the highest adsorbed oil (.057g) among the three cell densities and showed significant difference at p=.01 but comparable to the control (.066g) In terms of biomass concentration, all cell densities showed no significant difference at p=.01. Thraustochytrid is a promising tool during oil spill because it has the capacity to adsorb oil.
Keywords: Thraustochytriales; Oil spills